A Research to Determine The Burnout Level of Elementary School Supervisors Working in GAP Region - Refik-Adnan BALAY- ENGİN (Ankara Üniversitesi Eğitim Bilimleri Fakültesi Dergisi, 2007)
This study aims to determine the level of burnout feelings of supervisors working in GAP region. The population of the research composed of elementary school supervisors who were serving in the cities of the Southeastern Anatolia Region. Since the research was done on the entire population, no sampling was needed to be applied. The Maslach Burnout Inventory developed by Maslach and Jackson (1981) was used to collect data about the level of burnout experienced by the elementary school supervisors. Results showed that in general the elementary school supervisors experienced a medium level of burnout. The results also show that the elementary school supervisors experience a medium level of burnout in the dimension of „emotional exhaustion‟, a low level of burnout in „depersonalization‟ accomplishment‟ they experienced a burnout somewhere around the border